(untitled) (Research, Society and Development, 2025)
Objective: To identify, in the scientific literature, the limits and possibilities of telemonitoring consultations in the doctor-patient relationship and their impacts on treatment adherence in medical consultations conducted through telemedicine systems. Methods: This is an integrative literature review, including articles published between 2014 and 2022 in Portuguese, English, and Spanish languages, with full-text availability. Bibliographic research was conducted in the Scientific Electronic Library Online (SCIELO) and PubMed (MEDLINE) databases, using Health Sciences Descriptors (DeCs): Treatment adherence, Doctor-patient relationship, and Telemonitoring, with combinations using the Boolean operator "AND." Results: 36 articles met the inclusion and exclusion criteria, of which 22 were related to the benefits found in telemonitoring consultations, and 18 presented difficulties encountered in this same mode of consultation. Conclusion: Telemedicine is gaining increasing prominence in the doctor-patient relationship, offering benefits to both parties. However, there are obstacles to be overcome with the primary goal of increasing treatment adherence.